Inovasi Bioetanol berbahan Limbah Ampas Tebu Dan Jerami Sebagai Sumber Bahan Baku - Roihan Habibie, Abdullah; Widayoko, Agus; Yesi Yuliani (SMA Trensains Muhammadiyah Sragen, 2025)
The increasing consumption of fossil fuels in Indonesia has triggered significant carbon dioxide (CO2) emissions, especially from motor vehicles, with emission rates reaching 67,568.26 g/30 minutes/km for motorcycles and 63,335.30 g/30 minutes/km for cars (Sudarti, Yushardi,, & Nur Kasanah, 2022). These emissions contribute to the greenhouse effect and global warming (Anggraeni, Desember 2015). Agricultural waste such as sugarcane bagasse and rice straw, which are abundant in Indonesia, hold great potential to be processed into bioethanol as an alternative fuel. This study utilizes these wastes through hydrolysis, fermentation, and distillation processes. Combustion tests show that bioethanol produces lower CO2 emissions compared to fossil fuels. Water content analysis results in a value of 1.35%, which complies with the Indonesian National Standard (SNI), setting the maximum water content at 2%. These findings align with Dady Sulaiman’s (2021) research, which highlights the relationship between water content and yeast concentration in fermentation. In conclusion, bioethanol derived from sugarcane bagasse and rice straw is not only environmentally friendly but also meets quality standards. With proper management, this bioethanol can serve as a sustainable fuel solution and support carbon emission reduction efforts.